Análise de sistemas de coleta e armazenamento de águas pluviais para fins não potáveis - Souza, Flavia Simões de (2014)
This paper aimed to address the Utilization of Waters of Rain theme, presenting methods and systems that enable their use, in order to show and educate people about the risks of shortages and possible problems that may be caused by the uncontrolled use of water, aimed to encourage people to use this system will bring many benefits because it is a simple solution that allows you to preserve drinking water. For this was used as the main methodology to bibliographic search.